(untitled) (Fiep Bulletin - online, 2014)
Growing levels of obesity have revealed important health problems to society. Knowing the BMR can help the stablishment of important basis to evaluate the energy expenditure, which is related to weight gain or loss. Therefore, knowing the BMR values seems to be one of the first steps to criate a valid weight control program. The general objective of this work is reviewing the studies with the prediction equations of Basal Metabolic Rate proposed by Harris-Benedict (1919), Schofield (1985) and FAO/WHO/UNU (1985), pointing out the main differences between the estimaded values through the equations and the values measured by indirect calorimetry. The review has found several cases in which the equations to predict the BMR were inadequate. So, obtaining more information about the basal methabolism of different populations, living in different places in the world is very necessary to better evaluate and interpretate the results obtained by the equation, because it is important to understand the energetic needs of each individual to take the first step in control of health conditions such as obesity.